Relationship of Infant-Child Mortality to Fertility: Some Theoretical and Empirical Considerations Relevant to Pakistan (Review Article) (The Pakistan Development Review, 1974)
Of considerable interest to social scientists, particularly the demogra¬phers, is the process of family limitation—a critical link in the demographic transition from high to low fertility. The available literature identifies numerous macro socio-economic and cultural variables found to be correlated with fertility behaviour [9]. However, little is known regarding the key motivational factors which, by impinging upon individual couples, result in a reduction of family size. The advocates of family planning programmes claim that family limitation can be achieved by providing couples with information about contraception along with effective means of birth control. The critics of current family planning programmes while recognising the importance of accessibility of effective contraception in family limitation, however, strongly feel that the reduction in fertility of the developing countries may not be achieved without substantial social, economic and cultural changes in those countries. These changes, among other things, are postulated to result in a substantial decline in levels of mortality—a generally accepted antecedent condition for substantial decline in fertility.